Determination of the FIFO-stack size for the algorithm of the image region growing - V. Yu. Tsviatkou (Системный анализ и прикладная информатика)
The aim of the work is to derive an expression that allows determining the size of the FIFO-stack for storing the coordinates of adjacent pixels depending on the image size for the segmentation algorithm based on region growing. The FIFO stack, organized on the principle of a ring multi-bit shift register, is considered. The conditions for maximum loading of the FIFO stack are formulated, for which an expression is obtained that allows one to accurately determine the required size of the FIFO stack, which provides memory savings.